Evaluation of diazepam nasal spray in patients with epilepsy concomitantly using maintenance benzodiazepines: An interim subgroup analysis from a phase 3, long‐term, open‐label safety study. (4th May 2021) - Segal, Eric B.; Tarquinio, Daniel; Miller, Ian; Wheless, James W.; Dlugos, Dennis; Biton, Victor; Cascino, Gregory D.; Desai, Jay; Hogan, R. Edward; Liow, Kore; Sperling, Michael R.; Vazquez, Blanca; et al.
Abstract: Objective: Diazepam nasal spray (Valtoco), indicated for acute treatment of frequent seizure activity (seizure clusters) in patients with epilepsy ≥6 years of age, is designed to be a rapid, noninvasive, socially acceptable route of administration. This interim analysis evaluated the safety profile of diazepam nasal spray in patients with and without concomitant use of benzodiazepines, with use of a second dose for a seizure cluster as a proxy for effectiveness. Methods: A long‐term, phase 3, open‐label safety study enrolled patients with epilepsy who had seizures despite a stable antiseizure medication regimen. Results: Among 175 patients enrolled by October 31, 2019, a total of 158 were treated with diazepam nasal spray (aged 6–65 years; 53.8% female). Of those, 119 (75.3%) received concomitant benzodiazepines (60, chronic; 59, intermittent); 39 (24.7%) did not. Use of a second dose was similar in patients using chronic concomitant benzodiazepines (second dose in 11.1% [144/1299]) and those with no concomitant benzodiazepines (second dose in 10.3% [41/398]). Treatment emergent adverse events (TEAEs) occurred for 80.0% with chronic use of concomitant benzodiazepines and 61.5% without. Cardiorespiratory depression was not reported, and no serious TEAEs were treatment related. Study retention was high: 83.3% in the chronic benzodiazepine group and 76.9% in the no‐benzodiazepine group. Findings were similar in a sub‐analysis of patients who were ( n = 44) or were not ( n = 75) taking clobazam. Significance: This analysis of patients from a long‐term study shows a similar safety profile of diazepam nasal spray in patients with and without concomitant benzodiazepines, and consistent with the established profile for diazepam. Use of a single dose of diazepam nasal spray and high study retention rates suggest the effectiveness of diazepam nasal spray in patients irrespective of chronic daily benzodiazepine use. Results were similar in the clobazam sub‐analysis. These results support the safety and effectiveness of diazepam nasal spray in patients with concomitant benzodiazepine use.